POWER GENERATION AND STORAGE SYSTEM ADAPTED TO A MEDICAL BICYCLE - Druga, Corneliu (ACTA TECHNICA NAPOCENSIS - Series: APPLIED MATHEMATICS, MECHANICS AND ENGINEERING, 2018)
The paper presents the design and construction of a power generation and storage system adapted to a medical bicycle (model 70 years), located in the Medical Engineering Laboratory of Transylvania University. Mostly the system consists of a car alternator (synchronous generator), voltage inverter, car storage battery and a digital multimeter. The rotation movement from the bicycle to the alternator is transmitted via a rubber trapezoid strap. The voltage inverter converts the approximately 14.2 V DC (from the alternator output) into alternating current 220V (at the inverter output). Although the system has a simple construction and a low cost price it has a very good efficiency being very useful in the Laboratory of Medical Engineering.
Keywords: bicycle; inverter; synchronous generator; storage battery.